HUBUNGAN TINGKAT PENGETAHUAN MENGENAI DIET HIPERTENSI TERHADAP KEJADIAN HIPERTENSI PADA LANSIA DI PUSKESMAS BALOI PERMAI BATAM KOTA - Brain Guntoro; Kasih Purwati (Universitas Batam, 2019)
Hypertension is one of the number one causes of death and disability in the world. Hypertension contributes nearly 9.4 million deaths from cardiovascular disease each year. Hypertension can cause undesirable effects, it needs good handling, one of them is by doing a hypertension diet. To carry out a hypertension diet requires knowledge, lack of knowledge can increase risk factors for hypertension. This study aims to determine the relationship of the level of knowledge about hypertension diet to the incidence of hypertension in the elderly at the Baloi Permai Public Health Center Batam City. This research method is an analytic observational with a cross-sectional approach conducted at the Baloi Permai Public Health Center Batam City 2018. Sampling technique is a total sampling with a sample of 64 people in 2018 determined by inclusion and exclusion criteria. The results of the study were analyzed with frequency distribution and then tested with the Chi-square test. Based on the results of this study indicate that of the 64 respondents found elderly who have a good level of knowledge are 41 people (64.1%), 48 people (75.0%) have an age range between 60-70 years. 27 people (42.2%) elderly have the last high school education and 40 people (62.5%) have jobs as entrepreneurs. Elderly people who have normal blood pressure are 40 people (62.5%), and those affected by hypertension are 24 people (37.5%). The elderly who have a family history of hypertension is 21 people (32.8%) and those who do not have a history of hypertension are 43 people (67.2%). Chi-Square Test analysis results show the significance value p = 0.009. This number is significant because the p-value is smaller than the significance level (Î±) â‰¤ 5% (0.05), so H0 is rejected and Ha is accepted. Therefore it can be concluded that there is a significant relationship about the level of knowledge about the hypertension diet to the incidence of hypertension in the elderly. From the results of this study it was concluded that there was a relationship between the level of knowledge about the hypertension diet and the incidence of hypertension in the elderly at the Baloi Permai Public Health Center Batam City in 2016.